I-CReST 2021 International Conference on Research and Practices in Science, Technology and Social Sciences: proceeding book - Ahmad Baidowi, Zaid Mujaiyid Putra (Center of Foundation Studies, 2021)
The Centre of Foundation Studies, Universiti Teknologi MARA (UiTM), Malaysia held its 2nd International Conference (I-CReST 2021) on 26 June 2021. With the theme, “Embracing Research Culture and Fostering Academic Excellence”, the conference provided a platform for undergraduate and postgraduate students, academics, researchers, professionals, and industrial practitioners from various backgrounds to share ideas and research findings in their respective fields. A total of 130 papers were presented by academics from local institutions, while 10 papers were from international educational institutions, for example from, India, Indonesia and Russia.